The promotion of moral development in early childhood education: a recent systematic review - Md Kambali, Intan Diyana; Abd Karim, Aishah Hanim; Ismail, Halim; Yusof, Ummu Hani (https://www.masree.info/journal/irjes/current/, 2026)
This systematic literature review explores how moral development is cultivated in early childhood education, a pivotal stage for shaping ethical reasoning, social responsibility, and character formation. Despite growing academic interest, research on this topic remains fragmented across psychological, pedagogical, and sociocultural disciplines, hindering a comprehensive understanding of effective moral education practices. Guided by the PRISMA framework, a systematic search was conducted in the Scopus and Web of Science databases using Boolean operators and predefined inclusion criteria. The keywords "moral development" and "preschool" were applied, resulting in 39 peer-reviewed articles published within the past eight years. Critical analysis and synthesis of these studies revealed three dominant themes. The first theme, Psychological and Developmental Foundations of Moral Growth, emphasises the roles of cognitive, emotional, and behavioural factors framed by classical theories such as those of Piaget and Kohlberg. The second theme, Pedagogical and Institutional Practices in Moral Education, examines the contribution of teachers, curricula, and institutional culture in promoting moral learning through modelling, explicit teaching, and value-oriented classroom practices. The third theme, Cultural, Familial, and Societal Influences, highlights how home environments, cultural traditions, and community norms shape children's moral reasoning and prosocial behaviour. Collectively, the findings affirm that moral development in early childhood is a multifaceted process requiring integrative approaches that combine individual, educational, and contextual dimensions. Future research should advance culturally responsive pedagogies, foster collaborative engagement between educators and families, and employ longitudinal designs to enhance moral education implementation in early learning settings.